2019
DOI: 10.1103/physreve.100.022305
|View full text |Cite
|
Sign up to set email alerts
|

Social reinforcement with weighted interactions

Abstract: The speed and extent of diusion of behaviors in social networks depends on network structure and individual preferences. The contribution of the present study is twofold. First, we introduce weighted interactions between potential adopters that depend on the similarity in their preferences and moderate the strength of social reinforcement. The reason for the extension is the existence of a conrmation bias in the way agents treat information by prioritizing evidence conforming to their opinion. As a result, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…This can build on earlier work (Schuldt et al, 2019;Goldberg et al, 2019;Rohring and Akerlof, 2020). Furthermore, it might be worth investigating how social media use and social networks (Konc and Savin, 2019) shape a person's social perceptions. Many people nowadays get their news and information in general and specifically on climate change from like-minded peers in online environments (Williams et al, 2015), which may further amplify the identified biased perceptions.…”
Section: Discussionmentioning
confidence: 87%
“…This can build on earlier work (Schuldt et al, 2019;Goldberg et al, 2019;Rohring and Akerlof, 2020). Furthermore, it might be worth investigating how social media use and social networks (Konc and Savin, 2019) shape a person's social perceptions. Many people nowadays get their news and information in general and specifically on climate change from like-minded peers in online environments (Williams et al, 2015), which may further amplify the identified biased perceptions.…”
Section: Discussionmentioning
confidence: 87%
“…21 For more discussion of a social norm diusing through weighted social interactions see Konc and Savin (2019). at 20,000 and the maximum income at 1,000,000.…”
Section: Income Distributionmentioning
confidence: 99%
“…The importance of this issue to our understanding of different aspects of social cohesion has been recently highlighted in an agent-based framework by scholars such as Sobkowicz (2018) and Konc and Savin (2019) . Having greenhouse gas mitigation practices as general benchmark and applying tools from network theory, the latter modelled weighted interactions among agents that depend on the similarity in preferences.…”
Section: A Model Of Green Confirmation Biasmentioning
confidence: 99%
“…The latter occurs when a slight change in a system's parameters causes a new periodic trajectory to emerge from an existing periodic trajectory, the new one having double the period of the original. With the doubled period, it takes twice as many iterations for the numerical values visited by the system to repeat themselves (for a rigorous assessment, see Kuznetsov, 2004 ).…”
Section: A2 Proof Of Propositionmentioning
confidence: 99%